Transitioning into a Professional Teacher: EFL Preservice Teachers' Anxiety in Teaching Practicum - Mardhatillah, Mardhatillah; Widiati, Utami; Sujiatmoko, Ahmad Heki (ETERNAL (English Teaching Journal), 2024)
Foreign language anxiety has been proven to be an important issue in language learning, according to research on language learning in foreign languages. This study aims to determine the level of anxiety experienced by English preservice teachers. Most research projects in the past concerned learners’ anxiety about students who learning English. To fill the gap, the current study tries to deliver a different perspective on classroom anxiety. Thus, the current study investigates anxiety from preservice teachers’ points of view quantitatively. The current study examines the level of anxiety by adopting the Foreign Language Teaching Anxiety Scale (FLTAS) by Yoon (2012). Next, the scale in the form of a questionnaire has been responded to by 27 English preservice teachers. Further, the results show that the preservice teachers have a moderate level of anxiety. Overall, the study outlines the principal factors causing and affecting preservice anxiety about teaching English as a foreign language in the classroom